2003
DOI: 10.1295/polymj.35.422
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Poly(ε-caprolactone) Using Yttrium Triflate

Abstract: ABSTRACT:The ring-opening polymerization of ε-caprolactone (CL) has been initiated by yttrium triflate (trifluoromethanesulfonate) in air using simple glass vials at 60• C without desiccation steps and stirring. The number averaged molecular weight and molecular weight distribution of the obtained poly(ε-caprolactone) (PCL) was 5000-12000 and about 1.2, respectively. It was found that this polymerization reaction of CL was activated by the addition such as little water or 2-propanol. The copolymerization activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…However, not all the catalysts can tolerate the presence of water, for example: (1) aluminum isopropoxide (Al(O-iPr) 3 ) catalyst was hydrodegraded by water, obtaining an Al compound without polymerization activity to CL [27]; (2) tin octoate (tin(II) 2-ethylhexanoate, (Sn(Oct) 2 )) in the presence of water leads to the formation of macrocyclic species of PCL [28] Based on the observed selectivity, short reaction times (ca. 2 h) and good yields (98%) obtained when Dec is used as catalyst, we can conclude that Mo 10 O K8 34 is the best choice among the other molybdenum derivatives studied to be used in ROP of CL.…”
Section: Homopolymerization Of CL By Molybdenum Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all the catalysts can tolerate the presence of water, for example: (1) aluminum isopropoxide (Al(O-iPr) 3 ) catalyst was hydrodegraded by water, obtaining an Al compound without polymerization activity to CL [27]; (2) tin octoate (tin(II) 2-ethylhexanoate, (Sn(Oct) 2 )) in the presence of water leads to the formation of macrocyclic species of PCL [28] Based on the observed selectivity, short reaction times (ca. 2 h) and good yields (98%) obtained when Dec is used as catalyst, we can conclude that Mo 10 O K8 34 is the best choice among the other molybdenum derivatives studied to be used in ROP of CL.…”
Section: Homopolymerization Of CL By Molybdenum Compoundsmentioning
confidence: 99%
“…It has been reported that some organolanthanides form adducts with BL [30], and in some cases linear diolate [31]. For copolymerization of BL and CL, Kunioka found that addition reactions of BL (comonomer) cause deactivation of yttrium catalyst to ROP of CL [27]. Bulk copolymerization of CL with BL was achieved using ammonium decamolybdate (obtained in situ, Section 2) as catalyst with a M/HepZ20,000 (where MZCLCBL) at 150 8C by 2 h. Copolymers with different compositions, as a function of the used feed ratio CL:BL, were obtained ( Table 2).…”
Section: A-hydroxylic-u-(carboxylic Acid) Poly(3-caprolactoneco-g-butmentioning
confidence: 99%
“…wavenumber range of sample containing 1% (wt) of AgSbF6 and 2% (wt) of DPSi in TMPTA under air (1-before and 2-after polymerization). However, the great interest of the proposed approach lies on the fact that the initiating system is efficient using simple glass vials and unpurified TMPTA, even in the presence of water or oxygen, which can act as polymerization inhibitors with other synthetic approaches [50]. This can open new opportunities for mass production and applications of PTMPTA.…”
Section: Free Radical Polymerization (Frp)mentioning
confidence: 99%
“…Small‐ and medium‐size (di)lactones (4, 6, and 7‐membered) can relatively easily be polymerized because of their large ring‐strains. Many catalysts and/or initiators have been developed for the ROP of this class of cyclic ester monomers 1–6. On the other hand, ROP of macrolactones such as 16‐membered ω‐pentadecalactone (PDL) has been less explored.…”
Section: Introductionmentioning
confidence: 99%